Plant ethnoveterinary practices in two pyrenean territories of catalonia (iberian peninsula) and in two areas of the balearic islands and comparison with ethnobotanical uses in human medicine. - Carrió, Esperança; Rigat, Montse; Garnatje, Teresa; Mayans, Marina; Parada, Montse; Vallès, Joan (Evidence-based complementary and alternative medicine : eCAM, 2012)
This paper presents the results of an ethnobotanical study centred in veterinarian uses in two Catalan Pyrenean regions (Alt Empordà -AE- and High River Ter Valley -AT-, Iberian peninsula) and two Balearic Islands areas (Formentera -FO- and northeastern Mallorca -MA-). In the areas studied, 97 plant species have been claimed to be useful for veterinary purposes. A total of 306 veterinary use reports have been gathered and analysed. The ten most reported plants are Tanacetum parthenium (24 use reports), Parietaria officinalis (15), Ranunculus parnassifolius (14), Meum athamanticum (13), Olea europaea (13), Quercus ilex (12), Ruta chalepensis (12), Sambucus nigra (10) and Thymus vulgaris (10). According to comprehensive reviews, a high number of novelties for plant ethnoveterinary are contributed: 34 species and one subspecies, 11 genera, and three families have not been reported in previous works in this field, and 21 species had only been mentioned once. Several ethnoveterinary uses are coincidental with those in human medicine. Although ethnoveterinary practices are less relevant than in the past in the territories considered, as in all industrialised countries, the knowledge on plant properties and applications is still rich and constitutes a large pool of evidence for phytotherapy, both in domestic animals and humans.
The following values have no corresponding Zotero field: accession-num: 22829861
Keywords: Ethnobotany; medicinal plants (PG); Veterinary medicine

Traditional plant use in the National Park of Cilento and Vallo di Diano, Campania, Southern, Italy. - Di Novella, Riccardo; Di Novella, Nicola; De Martino, Laura; Mancini, Emilia; De Feo, Vincenzo (Journal of ethnopharmacology, 2012)
AIM OF STUDY: This paper reports an ethobotanical survey of the traditional uses of medicinal and useful plants in an area of the National Park of Cilento and Vallo di Diano, Campania, Southern Italy. MATERIALS AND METHODS: This study conducted between 2009 and 2011, gathered information on the medicinal plants traditionally used in Southern Italy (Campania Region). In all, we interviewed 70 key informants, whose age ranged between 50 and 85 years. This people belonged to families which had strong links with traditional activities of the area. RESULTS: The research resulted to the identification of 192 plants belonging to 64 families. Among the species reported, 86 are used in human medicine, 15 in veterinary medicine, 69 as human foods, 18 as animal feed, 61 for domestic and 8 for agricultural uses. CONCLUSION: A survey of the available literature on Southern Italy ethnobotany reveals that some species have been never reported and about 10% of cited uses are new. Data obtained show that in the studied area the folk use of plants is alive and still derives from daily practice.
The following values have no corresponding Zotero field: publisher: Elsevier accession-num: 23159473
Keywords: Agriculture; Agriculture: methods; Animal Feed; Animal Feed: utilization; Data Collection; Ethnobotany; Ethnobotany: methods; Ethnobotany: statistics & numerical data; Ethnomedicine; Food; Humans; Italy; Medicinal; Medicine; National Park of Cilento and Vallo di Diano; plant traditional uses; Plants; Traditional; Traditional: utilization; Veterinary medicine; Veterinary Medicine: methods

Ethnobotanical study of medicinal plants traditionally used in the Arribes del Duero, western Spain. - González, José a; García-Barriuso, Mónica; Amich, Francisco (Journal of ethnopharmacology, 2010)
Aim of the study: We studied traditional knowledge (TK) and current uses of medicinal plants among the inhabitants of the Arribes del Duero–ARD–(Spain), documenting traditional medical practices. Materials and methods:We interviewed 80 key informants (44 men and 36 women). Their average age was 72 years (range 48–98 years). We calculated the cultural importance for each species cited. To analyze how TK varies with the characteristics of the different informants, we performed an ANCOVA, taking the number of use-reports (URs) provided by each informant as a variable to model, and age and gender as explanatory variables. Results and conclusions: 156 medicinal remedies were recorded; they were based on a single species and were cited by at least three independent informants, and half of them are still in use today. These remedies are related to nine major organ systems and 54 therapeutic uses, and 70 species (belonging to 39 families) are used, most of which are herbs (64%). The most relevant family is the Lamiaceae (23 remedies, 8 species) and the species employed in the greatest number of remedies (8) is Urtica dioica L. However, the taxon with the greatest cultural value is Hypericum perforatum L. (CI = 0.71). 31% of the variability of the TK can be explained in terms of the age and gender of the informants (R 2 = 0.315), the age factor having a positive effect. Most of the remedies are related to the treatment of unimportant ailments, referring to disorders of the skin, and the respiratory and digestive systems. The leaves and fruits are the most frequently sought plant parts (40 and 17% of the plants mentioned, respectively), and infusions (34%) and decoctions (28%) are the main methods used for preparing the remedies. Likewise, we recorded remedies based on plant mixtures and ethnomedicinal novelties or rare uses, and comment on the inﬂuence exerted by superstition. Currently, many people preserve a rich TK about medicinal plants, and it may be afﬁrmed that the folk medicine is still very much alive in the ARD, above all as regards the treatment of certain common afﬂictions or unimportant ailments.
The following values have no corresponding Zotero field: accession-num: 20643201
Keywords: Ethnobotany; Medicinal plants; Quantitative analysis; Traditional remedies

On sweet acorn (Quercus spp.) cake tradition in Italian cultural and ethnic islands - Pignone, Domenico; Laghetti, Gaetano (Genetic Resources and Crop Evolution, 2010)
The CNR-IGV, over the last 15 years, has organized and performed expeditions aimed at collecting germplasm and local knowledge on plants used by local populations in isolated areas, such as geographical islands, or local communities that for ethnic or cultural reasons have maintained to a certain degree their isolation from surrounding populations (cultural islands). In two such cultural islands (Bovesia, Calabria region, south-west mainland Italy, and Ogliastra, Sardinia island, Italy) a tradition regarding the use of acorns for preparing a cake was recorded. In Ogliastra, an elder lady still retains the knowledge regarding the collections, maintenance and utilization of acorns for preparing a cake, a knowledge once common and now quite completely disappeared. The present paper reports on the culture associated to acorn used as a food for humans.
Keywords: acorn; Cultural islands; Ethnobotany; Neglected food; Quercus spp.

Medicinal plants in the Mediterranean area: synthesis of the results of the project Rubia. - González-Tejero, M R; Casares-Porcel, M; Sánchez-Rojas, C P; Ramiro-Gutiérrez, J M; Molero-Mesa, J; Pieroni, A; Giusti, M E; Censorii, E; de Pasquale, C; Della, a; Paraskeva-Hadijchambi, D; Hadjichambis, a; et al. (Journal of ethnopharmacology, 2008)
Within the scope of the European project RUBIA (ICA3-2002-10023), research has been performed on the traditional use and handling of plant species in several Mediterranean countries, Albania, Algeria, Cyprus, Egypt, Italy, Morocco, and Spain. This paper synthesises the chief results related to the medicinal utilization of those plants.
Keywords: Ethnobotany; Medicinal; Medicinal plants; Mediterranean; Mediterranean Region; Plants; Species Specificity

Ethnobotany of Montseny biosphere reserve (Catalonia, Iberian Peninsula): plants used in veterinary medicine. - Bonet, M Angels; Vallès, Joan (Journal of ethnopharmacology, 2007)
The present paper deals with plants used in veterinary medicine in Montseny. An ethnobotanical survey was carried out in the Montseny massif, which is situated in north-east Catalonia (Iberian Peninsula), covers 826 km(2) and has a population of 80,000. The information was obtained through 120 ethnobotanical interviews to 180 informants. Out of 584 species reported, 351 are claimed to be used in the health field (human and veterinary medicine), 280 in human and animal food and 236 have another kind of popular use. Medicinal species represent around 16.5% of Montseny's vascular flora. In a previous paper we addressed plant use in human medicine, and the present paper deals with veterinarian uses. As a reflection of the importance of rural life in the region, at least until recent times, a substantial number of medicinal plants (89 species, representing 6% of the flora of the territory and 6.4% of all medicinal use-reports in the region) is used in veterinary medicine. These remedies are mostly for cows, calves, sheep, pigs and horses, and secondarily, to poultry, rabbits and dogs. The main ailments treated are postnatal problems, intestinal troubles, wounds and dermatological problems. In many cases, the use of these remedies in veterinary medicine is fully consistent with their use in human medicine.
Keywords: Catalonia; Ethnobotany; Ethnoveterinary; Medicinal plants; montseny; Traditional knowledge

Ethnobotany of Montseny biosphere reserve (Catalonia, Iberian Peninsula): plants used in veterinary medicine. - Bonet, M. Angels; Vallès, Joan (Journal of ethnopharmacology, 2007)
The present paper deals with plants used in veterinary medicine in Montseny. An ethnobotanical survey was carried out in the Montseny massif, which is situated in north-east Catalonia (Iberian Peninsula), covers 826 km(2) and has a population of 80,000. The information was obtained through 120 ethnobotanical interviews to 180 informants. Out of 584 species reported, 351 are claimed to be used in the health field (human and veterinary medicine), 280 in human and animal food and 236 have another kind of popular use. Medicinal species represent around 16.5% of Montseny's vascular flora. In a previous paper we addressed plant use in human medicine, and the present paper deals with veterinarian uses. As a reflection of the importance of rural life in the region, at least until recent times, a substantial number of medicinal plants (89 species, representing 6% of the flora of the territory and 6.4% of all medicinal use-reports in the region) is used in veterinary medicine. These remedies are mostly for cows, calves, sheep, pigs and horses, and secondarily, to poultry, rabbits and dogs. The main ailments treated are postnatal problems, intestinal troubles, wounds and dermatological problems. In many cases, the use of these remedies in veterinary medicine is fully consistent with their use in human medicine.
The following values have no corresponding Zotero field: accession-num: 17059874
Keywords: Catalonia; Ethnobotany; Ethnoveterinary; Medicinal plants; montseny; Traditional knowledge

Folk phytotherapeutical plants from Maratea area (Basilicata, Italy). - Guarrera, Paolo Maria; Salerno, Giovanni; Caneva, Giulia (Journal of ethnopharmacology, 2005)
Field ethnobotanical survey was undertaken for the period of 2002-2003 in the Tyrrhenian part of the Basilicata region of southern Italy. Data of 56 species of plants belonging to 29 families where gathered through interviews; among the species, 47 are used in human therapy, 6 as insect repellents, 15 in veterinary medicine, 1 for its ichthyotoxic properties and 3 for magic therapeutic purposes. The most important findings in ethnomedicine relate to Nasturtium officinale (renal colic, liver diseases), Foeniculum vulgare subsp. piperitum (mouth ulcers), Leopoldia comosa (toothache, headache), Micromeria graeca subsp. graeca (coughs) and Ceterach officinarum (malaria), while in the ethnoveterinary field, we have Pteridium aquilinum (wolf bites) and Spartium junceum (fractures of animal limbs).
Keywords: Abdominal Pain; Abdominal Pain: drug therapy; Anthelmintics; Anthelmintics: therapeutic use; Antiparasitic plants; Basilicata; Common Cold; Common Cold: drug therapy; Cough; Cough: drug therapy; Diuretics; Diuretics: chemistry; Diuretics: therapeutic use; Ethnobotany; Ethnopharmacology; Ethnopharmacology: methods; Furunculosis; Furunculosis: drug therapy; Geography; Humans; Italy; Lung Diseases; Lung Diseases: drug therapy; Medicinal; Medicinal plants; Medicinal: classification; Medicine; Phytotherapy; Plant Preparations; Plant Preparations: therapeutic use; Plants; Skin Diseases; Skin Diseases: drug therapy; Time Factors; Traditional; Veterinary plants; Wound Healing; Wound Healing: drug effects; Wounds and Injuries; Wounds and Injuries: drug therapy

Studies on pharmaceutical ethnobotany in the regions of L'Alt Empordà and Les Guilleries (Catalonia, Iberian Peninsula). - Bonet, M a; Parada, M; Selga, A; Vallès, J (Journal of ethnopharmacology, 1999)
An ethnobotanical survey was carried out in two regions (L'Alt Emporda and Les Guilleries), situated in North East Catalonia (Iberian Peninsula), with an approximate area of 800 km2 and a population of 68000. Through interviews with 73 people, data was obtained on the medicinal uses of 220 species. The most important findings are presented here concerning the ethnopharmacology of those areas. One hundred and ninty four unreported or uncommon uses corresponding to 101 plant species were detected.
Keywords: Catalonia; Ethnobotany; Folk medicine; Medicinal plants; Quantitative ethnobotany

Contribution to the knowledge of the pharmaceutical ethnobotany of La Segarra region (Catalonia, Iberian Peninsula). - Raja, D; Blanché, C; Vallès Xirau, J (Journal of ethnopharmacology, 1997)
An ethnobotanical survey was carried out in the region known as La Segarra, situated at the north east of the Iberian Peninsula, in the inner plains of Catalonia, with an area of 720 km2 and a population of 17000. Working with 29 people, data on uses of 142 species belonging to 54 botanical families were obtained and presented, of which 13 uses corresponding to nine plant species were previously unreported.
Keywords: Catalonia; Ethnobotany; Folk medicine; Medicinal plants